Bridging texts and traditions: *Tattvasiddhi and early Madhyamaka in Kumārajīva's context - Lin, Xueni (Acta orientalia Academiae Scientiarum Hungaricae, 2025)
The relationship between the *Tattvasiddhi and Madhyamaka has remained a central topic for centuries. Contemporary scholarship has predominantly focused on the philosophical commonalities between the *Tattvasiddhi and Madhyamaka. This paper, however, takes a philological approach, illuminating the relationship between the *Tattvasiddhi and Madhyamaka through the lens of Kumārajīva’s translation. Employing computational techniques to uncover phraseological and philological evidence, this paper argues that Harivarman - the author of the *Tattvasiddhi - and the pioneers of the Madhyamaka school as represented in Kumārajīva’s Madhyamaka corpus, share some literary sources, like sūtra sources and analogies, respectively indicative of the geographical proximity and shared argumentation traditions.